2011
DOI: 10.1534/genetics.111.129841
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Caenorhabditis elegans to Hydrogen Sulfide and Hydrogen Cyanide

Abstract: Hydrogen sulfide (H2S), an endogenously produced small molecule, protects animals from various stresses. Recent studies demonstrate that animals exposed to H2S are long lived, resistant to hypoxia, and resistant to ischemia–reperfusion injury. We performed a forward genetic screen to gain insights into the molecular mechanisms Caenorhabditis elegans uses to appropriately respond to H2S. At least two distinct pathways appear to be important for this response, including the H2S-oxidation pathway and the hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 46 publications
6
112
0
Order By: Relevance
“…1, C and D). The tm3378 allele of sqrd-1 is a 445 bp deletion that removes exon two and is a predicted molecular null (13). We confirmed the previous observation that sqrd-1(tm3378) mutant animals die when exposed to H 2 S (13), though we found that it takes at least 10 h before sqrd-1(tm3378) mutant animals succumb in 50 ppm H 2 S. For this reason, we only measured translation for up to three hours of H 2 S exposure, at which time sqrd-1(tm3378) animals were mobile and visibly indistinguishable from untreated animals and wild-type controls.…”
Section: Resultsmentioning
confidence: 99%
“…1, C and D). The tm3378 allele of sqrd-1 is a 445 bp deletion that removes exon two and is a predicted molecular null (13). We confirmed the previous observation that sqrd-1(tm3378) mutant animals die when exposed to H 2 S (13), though we found that it takes at least 10 h before sqrd-1(tm3378) mutant animals succumb in 50 ppm H 2 S. For this reason, we only measured translation for up to three hours of H 2 S exposure, at which time sqrd-1(tm3378) animals were mobile and visibly indistinguishable from untreated animals and wild-type controls.…”
Section: Resultsmentioning
confidence: 99%
“…Although regulation of animal PHD activity by iron availability is well-established [cobaltous ion induced erythropoiesis is proposed to be via PHD inhibition (41)], it has had less prominence. P. aeruginosa infections, which often occur in hypoxic niches, such as in the cystic fibrosis lung (42), can induce a HIF-mediated hypoxic response in eukaryotic cells by production of small molecule factors, which have been proposed to be cyanide (43). Pyocyanin induces HIF-α up-regulation in human cells (13), likely via PHD inhibition, at least in part by iron sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…The same effect was seen whether the exposure was to 2mM sodium metabisulfite for 48 hours or 30 mM sodium metabisulfite overnight. Exposure to hydrogen sulfide at the non-lethal concentration of 150 ppm causes a reversible state of suspended animation in C. elegans [242]. In order to test for reversible suspended animation in nematodes in response to a non-lethal exposure to sulfur dioxide a DSLR camera with a macro lens was used to take images in quick succession, which allowed for a more detailed analysis of behavior than is possible using WormScan (Appendix 5).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to H 2 S has also been shown to induce a reversible state of decreased metabolic rate and temperature and a reversible state of suspended animation in mice [37]. This reversible state of suspended animation in C. elegans [242]. Prolonged exposure to a slow-releasing H 2 S donor (GYY4137) results in cancer cell death [243,244], via a defective pH regulation that triggers an uncontrolled intracellular acidification, causing apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation